A Novel IHCP Calculation Scheme to Estimate Surface Heat Flux during Impinging Cooling - Yu-Wei Liu, and Chen-Kang Huang (International journal of automation and smart technology, 2025)
This study introduces a novel inverse heat conduction problem (IHCP) calculation scheme to solve the surface heat flux of a subject with impinging cooling. From measured temperature records, the unknown boundary condition can be derived with one of three proposed algorithms. The scheme can then be performed without multiple iterations, and is much faster than traditional methods for IHCP. An impinging cooling apparatus is established to demonstrate the proposed scheme. The apparatus is to experimentally explore three impinging patterns, three impinging positions, and three unknown boundary condition derivation algorithms. The experimental results show that the proposed calculation scheme actually saves calculation time, and provides more accurate results. The most suitable unknown boundary condition derivation algorithm is suggested for each combination of operating parameters.